The Hollow Umma: A Socio-Epistemic Critique of Mandaville’s Transnational Politics in the Age of Algorithms - Anam, Rifqi Khairul (Jisiera: The Journal of Islamic Studies and International Relations, 2026)
This study challenges the techno-optimist narrative regarding the transnational Muslim community by critically revisiting Peter Mandaville’s theory of Travelling Islam through a socio-epistemic lens. While early scholarship envisioned digital connectivity as a mechanism for the creative reimagining of the Umma, this research argues that the digital medium has engineered a condition identified as the Hollow Umma. Rather than facilitating a genuine democratization of knowledge, the digital sphere triggers a radical epistemological deregulation that actively replaces traditional Islamic meritocracy—anchored in scholarly lineage (Sanad) and qualified expertise (Ahl al-Dhikr)—with a democratic logic of quantity and virality. Furthermore, driven by the epistemic habits of Generation Z and their active reliance on social media as primary search engines, the locus of religious authority has drastically shifted from classical Ulama to "religious micro-celebrities." Drawing upon Khaled Abou El Fadl’s framework, the paper demonstrates how this socio-epistemic inversion empowers an authoritarian discourse based on digital popularity over authoritative, self-limiting scholarship. By synthesizing Heidegger’s philosophy of technology with Zuboff’s concept of instrumentarian power, the article diagnoses the emergence of Digital Taqlid—a pathological state where believers surrender intellectual sovereignty to algorithmic authority. Ultimately, the paper concludes that without a deliberate reclamation of epistemic agency via Digital Tahqiq, the transnational Umma risks being reduced to a simulacrum of solidarity governed by emotional capitalism